FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS KEMISKINAN RUMAH TANGGA DI SUMATERA BARAT - Jaka Afri; Syamsul Amar (Media Riset Ekonomi Pembangunan (MedREP), 2025)
The purpose of this study is to identify factors that can influence poverty in households in West Sumatra. The data used in this study are cross-sectional data from the 2023 National Economic Survey (SUSENAS). This study uses a logistic regression model to analyze the factors that influence the poverty situation of households living in West Sumatra. This study reveals that the level of education of the head of the household, household size, employment status of the head of the household and type of head of the household have a positive and significant effect on the poverty status of households in West Sumatra.